The politics of flexing soybeans: China, Brazil and global agroindustrial restructuring. Issue 1 (2nd January 2016) - Oliveira, Gustavo de L. T.; Schneider, Mindi
Abstract : The political geography of the global soybean complex is shifting. While the complex has long been controlled by US-based transnational corporations, new agribusiness actors, business logics and power relations rooted in South America and East Asia are emerging, based in part on commodity flexing. We explore how soybean flexing is shaping and being shaped by global restructuring of the soybean processing industry. Using the divergent histories and uses of soy in China and Brazil, we propose that in order to understand the changing soy landscape, we must examine the relationships between soy's multiple-ness and flexible-ness, the political economy of soy processing, and the relationships between crop 'flexors' – those powerful firms that control the soy complex – with each other and with governments. We demonstrate that the agribusiness actors who are gaining more control over the soy complex are doing so in part through flexing, and that the ability to flex may ultimately determine the trajectory of global agroindustrial restructuring. Finally, we raise questions and make suggestions for further research on flex crops.